Hypophosphatemic osteomalacia in von Recklinghausen neurofibromatosis: Case report and literature review - Gupta, Aman; Dwivedi, Abhishek; Patel, Priyanka; Gupta, Somya (Indian Journal of Radiology and Imaging, 2015)
Osteomalacia in neurofibromatosis is a rare entity and distinct from more common dysplastic skeletal affections of this disease. As a rule, it is characterized by later onset in adulthood. There is renal phosphate loss with hypophosphatemia and multiple pseudofractures in the typical cases. The hypophosphatemic conditions that interfere in bone mineralization comprise many hereditary or acquired diseases, all of them sharing the same pathophysiological mechanism-reduction in phosphate reabsorption by the renal tubuli. This process leads to chronic hyperphosphaturia and hypophosphatemia, associated with inappropriately normal or low levels of calcitriol, causing rickets in children and osteomalacia in adults.
Keywords: Hypophosphatemia; neurofibromatosis; osteomalacia; von Recklinghausen disease